Analisis Kesulitan Guru Kelas IV Dalam Penerapan Kurikulum Merdeka Pada Mata Pelajaran IPAS di SDN Se-Kecamatan Muko-Muko Bathin VII - Ahmad Ikmal; Subhanadri Subhanadri; Dhini Mufthi (CV. Master Literasi Indonesia, 2025)
This research is motivated by the challenges faced by teachers in implementing the Independent Curriculum, particularly in Natural and Social Sciences (IPAS) at the elementary school level. Therefore, the purpose of this study is to describe the difficulties experienced by fourth-grade teachers in implementing the Independent Curriculum in the IPAS subject at elementary schools in Muko-Muko Bathin VII District, analyze the contributing factors, and identify the efforts teachers have made to overcome these difficulties. This research used a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with four fourth-grade teachers from four purposively selected public elementary schools, representing schools with B and C accreditation. Data were analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that the difficulties experienced by teachers encompass three main aspects: (1) difficulties in understanding and planning science and science lessons based on the Independent Curriculum, particularly in developing teaching modules and implementing differentiated learning; (2) limited facilities and infrastructure, including limited access to digital devices and internet networks; and (3) challenges in classroom management, particularly in dealing with the diversity of student characteristics and abilities. Factors contributing to these difficulties include a lack of technical training, suboptimal support from the principal, and the school's geographic and social conditions. Efforts made by teachers include independent study, discussions with colleagues, utilizing local resources, and participating in online training. This research recommends strengthening structural support and practical training from the government to facilitate the implementation of the Independent Curriculum in elementary schools, particularly in non-urban areas.